Identifikasi Potensi Bahaya pada Area Peleburan Logam Menggunakan Metode Hazard Identification Risk Assesment And Risk Control (HIRARC) dan Fault Tree Analysis (FTA) di CV. Barokah Logam Sejahtera - Syahrul Faiz; Ferida Yuamita (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
CV Barokah Logam Sejahtera is a company engaged in metal casting. CV Barokah Logam Sejahtera, where in 2022 there have been 3 work accidents, and in 2023 there has been 1 work accident. This study aimed to identify potential hazards in the smelting area and then calculate the risk of work accidents as an effort to minimize work accidents at CV Barokah Logam Sejahtera. Hazard Identification Risk Assessment and Risk Control (HIRARC) is a method for preventing or minimizing work accidents divided into 3 stages, namely hazard identification, risk assessment, and risk control. Fault Tree Analysis (FTA) is a simple fault tree analysis that can be described as an analytical technique. From the results of the analysis, there are 13 potential hazards with risk level categories, namely 1 risk extreme, 3 risk high, 7 risk moderate, and 2 risk low from 3 activities in the smelting area. For high risk, namely the potential danger of being crushed by a load and exposed to splashes of hot metal liquid. As for the causes of work accidents, such as CV Barokah Logam Sejahtera, it has the potential for work accident hazards. This occurs because PPE is inadequate and the work floor is dirty. In these activities there will be risks such as bruises, scratches and burns so that they can disrupt the production process because these incidents often occur and result in moderate injuries so they must be handled more seriously. As for administrative control efforts such as conducting briefings before work and providing first aid. Technical controls such as checking worker health and using PPE while in the smelting area such as safety shoes, masks, goggles and safety helmets, always be careful and keep the production floor clean